The Footnotes of European Thought: Slavery and Colonialism - Sezai Ozan Zeybek (İnsan & Toplum)
This article analyses Eurocentric narratives and how they overlook (and silence) par- ticular places and people. It covers a range of issues, starting from the Haitian plantations to the French Revolution; from the Enlightment philosophers’ ideas about colonialism to Marx’s understanding of how histories unfold. At first sight, these themes might seem unrelated, but they share an important aspect. As long as histories are told around particular subjects, that is, as the actions of those subjects, then other places, other times and other people will have to remain footnotes. They would not have an impact on the main story, or rather, the same stories can be told with or without them. In each theme, I look at the third degree actors and places which supposedly do not affect the dominant historical narratives. Yet, in this article, I argue that this problem does not only stem from Eurocentrism and that we need a more comprehensive examination of how we think of histories. I show that even the critical accounts of Eurocentrism repeat similar lines of thought, and that they often replace Europe with another centre. In order to challenge the boundaries of Europe, I will focus on and analyse those who are seen as outsid- ers (to European history) and ignored. I show that they are indeed part of the main story.